2010
DOI: 10.1089/dia.2010.0050
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Leakage Value in Relation to Pen Needle Length and Administered Dose After Subcutaneous Injection

Abstract: The needle length (between 12 mm and 4.5 mm) did not have a meaningful influence on the amount of leakage; however, significant differences with different needle lengths could be observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 6 publications
1
24
0
Order By: Relevance
“…21 Other studies have quantified skin leakage injections using needles as short as 4.5 mm and found only fractions of a unit of leakage (at most about 3.5% of the amount injected), even at injection volumes equivalent to 60 units-with the amount of leakage linked to dose, but not to needle length. [22][23][24] Many obese patients with type 2 diabetes have upper body segment fat distribution that is predominantly visceral; hence it cannot be assumed that there is excessive SC adipose tissue for injections in the thigh, 25,26 where minimum D was only 2.9 mm in our population. Furthermore, three-quarters of patients reported they inject insulin at 90°, and one-fourth indicated they do not pinch up at the thigh.…”
Section: Discussionmentioning
confidence: 86%
“…21 Other studies have quantified skin leakage injections using needles as short as 4.5 mm and found only fractions of a unit of leakage (at most about 3.5% of the amount injected), even at injection volumes equivalent to 60 units-with the amount of leakage linked to dose, but not to needle length. [22][23][24] Many obese patients with type 2 diabetes have upper body segment fat distribution that is predominantly visceral; hence it cannot be assumed that there is excessive SC adipose tissue for injections in the thigh, 25,26 where minimum D was only 2.9 mm in our population. Furthermore, three-quarters of patients reported they inject insulin at 90°, and one-fourth indicated they do not pinch up at the thigh.…”
Section: Discussionmentioning
confidence: 86%
“…However, reports of bent needles were infrequent, and insulin leakage was also rare in our study. Wittmann et al 19 reported that the needle length did not have a marked effect on the amount of insulin leakage. Their conclusions were based on an experimental model using pork rinds, and our results support their findings in humans.…”
Section: Discussionmentioning
confidence: 99%
“…8,[19][20][21] In 1 study, the volume of the injection did not affect the frequency of leakage. 3 In accordance with most previous studies, we found that larger Leakage data from the pig study.…”
Section: Leakage Influenced By Injection Techniquementioning
confidence: 99%
“…8 The relative amount of leakage did not differ for different injected volumes, which is also in line with a published study. 21 The reason for the injection volume dependency could be an increased tissue pressure on the insulin deposition from the surrounding subcutaneous tissue. Thereby, a larger amount of leakage could be pushed out of the needle puncture.…”
Section: Leakage Influenced By Injection Techniquementioning
confidence: 99%
See 1 more Smart Citation